IN VITRO AND IN VIVO ANTIINFLAMMATORY ACTIVITY OF THE METHANOLIC EXTRACT OF WHITE OYSTER MUSHROOM PLEUROTUS FLORIDA (MONT.) SINGER - MADHAIYAN PRABU; RENGANATHAN KUMUTHAKALAVALLI (International Journal of Pharma and Bio Sciences, 2014)
In vitro and in vivo antiinflammatory activities of methanolic extract of white oyster mushroom Pleurotus florida (Mont.) Singer were evaluated. The mushroom extract exhibited significant results for its inhibition of protein denaturation (69.30±4.98% at 1.0mg/ml); inhibition of proteinase activity (27.89±0.14% at 1.0mg/ml) in a dose-dependent manner and also antiinflammatory activity in Carrageenan induced acute inflammatory animal model (50.17% at 200mg/kg b.w). Presence of phytochemicals namely phenols, flavonoids, saponins and tannins may be responsible for such antiinflammatory activity. Results indicate that, white oyster mushroom may be used as a potential antiinflammatory agent.